PENGARUH AWALAN LARI 10 M DAN 20 M TERHADAP HASIL BELAJAR LOMPAT JAUH GAYA JONGKOK (STUDI PADA SISWA KELAS V SDN SIDOMULYO II KRIAN, SIDOARJO) - YAQIN, AINUL (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract In teaching physical education and health among affective, cognitive and psychomotor must be balanced in order to achieve the learning objectives perfectly. So far, there has been physical education learning process that only tends to psychomotor aspects. Based on the experience in learning process, the students are physically capable to do moving on well and get the maximum learning result. And it also must be accompanied by sufficient facilities. On the long jump matter, they were sometimes only provided dauntless jump course without counting running track used as starting. Therefore, prefix run was uncontrolled. Even though the prefix run is also one of the aspects in long jump, and can affects the learning result of long jump as whole. From the researcher’s observation in SDN Sidomulyo II Krian Sidoarjo, the activity of learning long jump, especially on a stage of start is not qualified yet. The purpose of this study is to find out: (1) the influence of starting run 10 meters and 20 meters towards the study result of long jump squat style of 5th graders in Sidomulyo II Elementary Shcool Krian Sidoarjo, (2) how big is the differences on the influence between starting run 10 meters and 20 meters towards the study result of long jump squat style of 5th graders Sidomulyo II Elementary Shcool Krian Sidoarjo. The objectives of this study were the students of class V Sidomulyo II elementary shcool Krian Sidoarjo taken for  35 students of class V A and 35 students of class V B. The methods of the analysis of this data was quantitative descriptive approach, while the data collection was done by testing the forward long jump squat style with the aspects of the observation include: starting, footstooling, jumping, and landing. The conclusion of this study are as follows: In accordance with the result of pretest and post test on the starting run 10 meters and 20 meters it showed an increase. Therefore, it can be concluded that there was an infuence between starting run 10 meters and 20 meters towards the result of jumping squat style of 5th graders in Sidomulyo II Elementary Shcool Krian Sidoarjo. By calculation correlation t test with significance level 0.05%, In the results of the different test between groups showed that ttest 0.195 < 2.000 ttable. It can be concluded that there was no difference between influence starting run 10 meters and 20 meters towards the study result of the long jump squat style of 5th graders Sidomulyo II Elementary Shcool Krian Sidoarjo Keywords: the starting run, the long jump squat style, the study result, elementary school.